Plato's Parmenides - Plato (Joan Palevsky imprint in classical literature., 2003)
Of all Plato's dialogues, the 'Parmenides' is notoriously the most difficult to interpret. Scholars of all periods have disagreed about its aims and subject matter. This work presents a translation of the dialogue together with an introduction and commentary which provides an explanation of the 'Parmenides'.